Nivolumab Versus Regorafenib in Patients With Hepatocellular Carcinoma After Sorafenib Failure - Kuo, Yuan-Hung; Yen, Yi-Hao; Chen, Yen-Yang; Kee, Kwong-Ming; Hung, Chao-Hung; Lu, Sheng-Nan; Hu, Tsung-Hui; Chen, Chien-Hung; Wang, Jing-Houng (Frontiers in Oncology, 2021)
Background: Nivolumab and regorafenib are approved second-line therapies for patients with hepatocellular carcinoma (HCC) after sorafenib failure. This study compared the effectiveness of nivolumab and regorafenib following sorafenib. Methods: We retrospectively enrolled HCC patients who had undergone nivolumab or regorafenib after sorafenib failure. Treatment response, treatment-related adverse events (TRAE) and clinical outcomes of study patients were recorded and analyzed. Results: A total of 90 patients (Male/Female: 67/23, mean age: 63 year) were enrolled, including 32 patients in the Nivolumab group and 58 patients in the Regorafenib group. The Nivolumab group had better objective response rates (16% vs 6.4%) and disease control rates (44% vs 31.9%) than the Regorafenib group, but there was no statistical difference. The comparison of time to progression (3.0 months vs 2.6 months, p=0.786) and overall survival (OS) (14 months vs 11 months, p=0.763) between Nivolumab and Regorafenib groups were also insignificant. Regarding number of TRAE incidences, the Nivolumab group was significantly lower than the Regorafenib group (37.5% vs 68%). After cession of nivolumab / regorafenib, 34 patients (37.8%) (Nivolumab group/ Regorafenib group: 11/23) could afford the following therapies. Concerning sequential systemic therapies, 17 patients (18.9%) received third-line therapy, whereas 6 patients (6.7%) could move to fourth-line therapy. In multivariable analysis, patients who achieved disease control were associated with improved OS (Hazard ratio, 0.18; 95% Confidence Interval, 0.07–0.46; p<0.001) after adjusting Child-Pugh class and post-treatment. Conclusions: After sorafenib failure, using nivolumab or regorafenib both illustrated promising treatment outcomes.